Performance of Fish Scale-Inspired Armour Subjected to Impact Loading by Different Impactor Shapes: A Numerical Investigation - Hari Bahadur Dura; Paul J. Hazell; Hongxu Wang (Materials Proceedings)
This paper investigates the impact performance of a hybrid scale–tissue structure inspired by elasmoid fish scales. Acrylonitrile butadiene styrene (ABS) acted as the hard scales, whereas thermoplastic polyurethane (TPU) mimicked the soft tissue. Low-velocity impact scenarios were investigated using a commercially available software, ANSYS LS-Dyna. The effect of indenter shape (conical, hemispherical, and flat head) was studied at three impact energy levels (50 J, 75 J, and 100 J). The specific energy absorbed for the conical indenter was the highest. The peak force for the conical, hemispherical, and flat-head indenters at an impact energy of 100 J was 6.0 kN, 5.4 kN, and 4.5 kN, respectively. The primary failure modes were shear failure and tensile breaking of the scales. The present study highlights the effect of indenter shape on the impact behaviour of a fish scale-inspired structure.